Analisis Aspek Lokalitas Mahmud Yunus dalam Tafsir Al-Qur'an Al-Karim - Muhammad Khai Hanif Yuli Edi Z; Halimatussadiyah Halimatussadiyah; Zulkipli Jemain (Jurnal Kajian Pendidikan Islam, 2023)
This article analyzes the aspects of locality in Mahmud Yunus' interpretation of the Noble Qur'an, Al-Karim. The interpretation has undergone 23 reprints and is recognized as an important work in the interpretation of the Qur'an in Indonesia. The study employs a historical-intertextual approach to explore the background of Mahmud Yunus' life, his social context, and the influence of his thoughts in the interpretation. Descriptive analysis is used to depict the local elements present in the interpretation. The analysis reveals three main aspects of locality in Mahmud Yunus' interpretation of the Noble Qur'an, Al-Karim. Firstly, there is locality in terms of language, with the use of local expressions such as "Lancar dikaji karena disebut" (Fluency in study comes from mentioning), and "Pandang anak pandang minantu" (Look at the child, see the son-in-law). Secondly, there is locality in general expressions, such as "Mulutmu harimaumu" (Your mouth is your tiger), and "Hemat pangkal kaya rajin pangkal pandai" (Thrifty leads to wealth, diligence leads to knowledge), Thirdly, there is locality in terms of socio-cultural aspects, with criticism of Minangkabau customs and education in Indonesia.The analysis of the aspects of locality in Mahmud Yunus' interpretation of the Noble Qur'an, Al-Karim, provides a deeper understanding of the influence of local elements in Qur'anic interpretation. This interpretation serves not only as a source of religious understanding but also reflects the cultural and social identity of the Minangkabau community. This research contributes significantly to the study of the Qur'an from a relevant local perspective in the context of Indonesian society.